THE IMPLEMENTATION OF PUBLIC SECTOR PERFORMANCE MEASUREMENT WITH BALANCED SCORECARD WITH STAKEHOLDER PERSPECTIVE (CASE STUDY ON RSUD DR. SOETOMO SURABAYA) - Hakim, Andik Lukman; Zaky, Achmad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Performance measurement is a benchmark of progress in achieving the goals and objectives that have been set previously. This research aims to measure the organization’s performance using the Balanced Scorecard with stakeholder perspective. The object of this research is Rumah Sakit Umum Daerah Dr. Soetomo Surabaya. This research is a descriptive qualitative research with case study approach. Balanced Scorecard perspective used in this research is financial perspective, stakeholder perspective, internal business process perspective, and growth and learn perspective. Measurement is done by comparing the realization with the target or ideal criteria that have been set. The comparison results are given a score for each indicator is then used to score each perspective. Based on the results, the ratio of the value of each perspective everything is above 1, which means that the overall realization of the performance exceeds the set targets. While the final score indicates that the stakeholder perspective has the highest value compared to other perspectives. This is consistent with the objectives of the organization that promotes the maximization of service to stakeholders. With these results it can be concluded that the performance of the organization in general can be said to be good.Keywords: performance measurement, balanced scorecard, and stakeholder perspective